2014
DOI: 10.1186/1756-8935-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific regulation of imprinted X inactivation in extraembryonic endoderm stem cells

Abstract: BackgroundSilencing of the paternal X chromosome (Xp), a phenomenon known as imprinted X-chromosome inactivation (I-XCI), characterises, amongst mouse extraembryonic lineages, the primitive endoderm and the extraembryonic endoderm (XEN) stem cells derived from it.ResultsUsing a combination of chromatin immunoprecipitation characterisation of histone modifications and single-cell expression studies, we show that whilst the Xp in XEN cells, like the inactive X chromosome in other cell types, globally accumulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…These studies revealed peculiar features of imprinted Xi chromatin and lower stability of iXCI. Enrichment of H3K27me3 on the Xi has been observed in all cells from the extra‐embryonic lineages , yet, to a lower extent compared to a randomly inactivated X: approximately 76–80% of X‐linked genes display female‐specific enrichment of H3K27me3 in XEN and TS cells, while this number reaches 93% in liver cells . This is in agreement with the observation that levels of H3K27me3 are globally lower in TS and XEN cells compared with post‐implantation embryonic stages .…”
Section: Are All Inactive X Chromosomes Equivalent?supporting
confidence: 87%
See 2 more Smart Citations
“…These studies revealed peculiar features of imprinted Xi chromatin and lower stability of iXCI. Enrichment of H3K27me3 on the Xi has been observed in all cells from the extra‐embryonic lineages , yet, to a lower extent compared to a randomly inactivated X: approximately 76–80% of X‐linked genes display female‐specific enrichment of H3K27me3 in XEN and TS cells, while this number reaches 93% in liver cells . This is in agreement with the observation that levels of H3K27me3 are globally lower in TS and XEN cells compared with post‐implantation embryonic stages .…”
Section: Are All Inactive X Chromosomes Equivalent?supporting
confidence: 87%
“…The inactive state of the Xp is, however, passed on and maintained, at least for the period of in utero life, in cells of the extra‐embryonic lineage. The maintenance and stability of iXCI in this post‐implantation context has mainly been addressed in vitro, through the analysis of cells derived from the trophectoderm (TS, trophoblast stem cells, and differentiated derivatives such as TGC, trophoblast giant cells) and from the primitive endoderm (XEN cells) – and in rare cases, from in vivo analyses . These studies revealed peculiar features of imprinted Xi chromatin and lower stability of iXCI.…”
Section: Are All Inactive X Chromosomes Equivalent?mentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP assays were performed as previously described [ 45 ] using an H3K27me3 antibody (07-449 from EMD Millipore, Billerica, MA, USA) and analysed as described previously [ 19 , 20 ]. ChIP-chip data have been deposited under Gene Expression Omnibus accession number [GSE:68536].…”
Section: Methodsmentioning
confidence: 99%
“…Paradoxically, this latter lineage is particularly rich in gene escaping from I-XCI—i.e. genes expressed from both Xs—compared to other adult cell types [ 18 , 19 ]. In addition to this, transient and spontaneous reactivations of certain X-linked genes occur both and ex vivo [ 20 ] and, after differentiation, the relaxation of I-XCI extends to additional genes in specific subtypes of placental cells [ 21 25 ].…”
Section: Introductionmentioning
confidence: 99%